Characterization of Soil Quality in Erosion Prone Environment of Ukpor, Nnewi-South L.G.A. of Anambra State, Nigeria - Ubuoh Emmanuel Attah; Akhionbare W. N; Oweremadu E.; Onifade O.A (Institute of Advanced Engineering and Science, 2013)
The study was conducted at Nnewi –South of Anambra State, Nigeria to characterize soil in erosion prone area in order to know nutritional values of the soil to enable farmers employ appropriate measures to conserving the soils for high productivity. Soil auger studies were made at three locations where traverse was cut.Three profile pits designated ECH/UK/ 01 (upper slope) , ECH/UK/ 02 (middle slope ) and ECH/UK/ 03 (lower slope) were sited and samples of soils were taken to test for physico-chemical properties of the soils. The results revealed that the soils are deep, well drained , dark reddish brown to reddish brown, and yellowish red of the Munsell color notation. The soil texture in the three pedons have coarse texture that ranged from sandy clay loam to sandy loam, with high percentage of sand which is the reflection of the parent material. The bulk density ranged between between 1.50 – 1.80 g/cm3,, soil pH (3.33 – 4.09) indicating very strong acidity status, O.C.(0.28 – 0.89%), O.M (0.48- 1.54%), total N ( 0.042 – 0.98%), Available P ( 2.80 – 11.00 mg.kg-1), Na+( 0.113 – 270cmol.kg-1), K+(0.036 – 0.087 cmol.kg-1), Mg++(0.80-5.60 cmol.kg-1), Ca++(0.42 – 10.40 cmol.kg-1), EA (0.24 -1.28 cmol.kg-1) CEC( 3.104 – 16.966 cmol.kg-1), and BS ( 80.28 – 96.06%) indicating low fertility rate of the soil due to heavy leaching and intensive agricultural activities that leads to erosion of the soil to devastating stage, which could be restored by reforestation programme, integrated Nutrient Management Options, and Effective public enlightenment campaign about the advantages of soil conservation for environmental sustainability.